2008
DOI: 10.1128/mcb.01405-07
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Specific Deletion of Rictor Impairs Insulin-Stimulated Glucose Transport and Enhances Basal Glycogen Synthase Activity

Abstract: Rictor is an essential component of mTOR (mammalian target of rapamycin) complex 2 (mTORC2), a kinase complex that phosphorylates Akt at Ser473 upon activation of phosphatidylinositol 3-kinase (PI-3 kinase). Since little is known about the role of either rictor or mTORC2 in PI-3 kinase-mediated physiological processes in adult animals, we generated muscle-specific rictor knockout mice. Muscle from male rictor knockout mice exhibited decreased insulin-stimulated glucose uptake, and the mice showed glucose intol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
148
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(170 citation statements)
references
References 59 publications
19
148
1
2
Order By: Relevance
“…This finding indicates that Rictor plays a major role in the regulation of the SGK1 signaling cascade, which has been suggested to be a primary effector of mTORC2's function in yeast (Kamada et al, 2005;Aronova et al, 2008) and Caenorhabditis elegans (Jones et al, 2009;Soukas et al, 2009), but suggests that it may be somewhat less critical in the regulation of the activity of Akt/PKB. It is noteworthy that in muscle-specific, Rictor-knockout mice, Akt/PKB phosphorylation at S473 is decreased, while phosphorylation of FOXO3A at T32 and FOXO1 at T24 is maintained (Bentzinger et al, 2008;Kumar et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that Rictor plays a major role in the regulation of the SGK1 signaling cascade, which has been suggested to be a primary effector of mTORC2's function in yeast (Kamada et al, 2005;Aronova et al, 2008) and Caenorhabditis elegans (Jones et al, 2009;Soukas et al, 2009), but suggests that it may be somewhat less critical in the regulation of the activity of Akt/PKB. It is noteworthy that in muscle-specific, Rictor-knockout mice, Akt/PKB phosphorylation at S473 is decreased, while phosphorylation of FOXO3A at T32 and FOXO1 at T24 is maintained (Bentzinger et al, 2008;Kumar et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Rictor, an important component of mTORC2, contributes to glucose homeostasis in murine muscle tissue (Kumar et al, 2008), TORC2 C. elegans mutants show modulation of lifespan by affecting feeding and metabolism of different diets (Soukas et al, 2009), TORC2 is a mediator of proliferative and survival signals in cancer cells (Fang et al, 2012) and a study in mouse embryonic fibroblasts showed that mTORC2 regulates the TLR-mediated inflammatory response via FoxO1 (Brown et al, 2011). In addition, PRR5L, which is part of mTORC2, has been suggested to play a role in apoptosis in HeLa cells, but whether it is pro-apoptotic or antiapoptotic remains unclear (Thedieck et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact cause of lethality is unknown, increased cell death was not readily apparent in the knockout embryos. To gain further insight into the tissue-specific functions of mTORC2, conditional knockout models of rictor have been developed, including skeletal muscle, white adipose tissue, and pancreatic b cells (Bentzinger et al 2008;Kumar et al 2008Kumar et al , 2010Cybulski et al 2009;Gu et al 2011). Although some metabolic defects are reported, there is no indication from these studies that mTORC2 loss-at least under otherwise normal physiological conditions-results in increased apoptosis.…”
Section: Mtorc2-dependent Cell Survival Pathwaysmentioning
confidence: 99%
“…The reason for this discrepancy remains unclear but may reflect a difference between acute knockdown and chronic knockout experiments, or the existence of a compensatory mechanism. Although phosphorylation at both T308 and S473 is required for maximal AKT activity in vitro, it appears that T308 phosphorylation alone empowers AKT with enough activity to phosphorylate many of its substrates in cultured cells or in tissues (Alessi et al 1996;Guertin et al 2006;Jacinto et al 2006;Yang et al 2006;Bentzinger et al 2008;Kumar et al 2008Kumar et al , 2010Cybulski et al 2009;Gu et al 2011).…”
Section: Mtorc2-dependent Cell Survival Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation